Reliability and validity of the revised indebtedness scale in Chinese university students - Jing Zhang; Rui Feng; Zheyan Li; Hongyu Liang; Tonglin Jin; Yunna A; Xiaoyu Li (Scientific Reports)
Abstract The purpose of this study was to evaluate the psychometric properties of the Chinese version of the Revised Indebtedness Scale (IS-R-C) in mainland China. A total of 1057 university students participated in this study using a two-wave whole-group sampling method. Sample 1, consisting of 537 participants, was used for item analysis and exploratory factor analysis (EFA) of the Revised Indebtedness Scale (IS-R). Sample 2, comprising 520 participants, was used for confirmatory factor analysis (CFA), reliability analysis and gender invariance test. To assess criterion validity, the Social Avoidance and Distress Scale (SADS), the Renqing Questionnaire (RQQ) and the Subjective Well-being Scale (SWBS) were administered. The results of the item analysis and EFA indicated that the IS-R-C comprises 12 items, delineated into two dimensions: pressure to repay and requirements for interaction. CFA further substantiated this two-factor model for the IS-R-C (χ 2 /df = 4.24, RMSEA = 0.079, GFI = 0.94, NFI = 0.91, IFI = 0.93, TLI = 0.91, CFI = 0.93 and SRMR = 0.062). The total score of the IS-R–C exhibited a significant positive correlation with both the SADS score (r = 0.34, p < 0.001) and the RQQ score (r = 0.34, p < 0.001). Additionally, it demonstrated a negative correlation with the SWBS score (r = -0.09, p < 0.05). The Cronbach’s α coefficient for the overall IS-R–C score was 0.88, indicating high internal consistency. The scale demonstrated a split-half reliability coefficient of 0.73 and a composite reliability coefficient of 0.91. The reliability coefficients for the two subscales were 0.77 and 0.87. Furthermore, the IS-R-C exhibited measurement invariance across gender identities. The IS-R-C demonstrates satisfactory psychometric properties, making it a suitable measure for studying indebtedness and related research in China.